(untitled) (Global Journal of Science Frontier Research, 2015)
Deforestation has a negative impact on the immediate environment and on the global scale, climate change. This paper is aimed at assessing the effect of deforestation to temperature and invariably on climate change in Nigeria. It discussed the rates of deforestation in Nigeria and globally; climate change in Nigeria; impact of extreme weather events in Nigeria; the effect of deforestation with respect to temperature change; the greenhouse gas (GHG) emissions attributed to deforestation in Nigeria; the obvious relationship between deforestation, temperature and climate change; and the mitigate measures to deforestation nationally and globally. The research considered an extended Eighty years period for this work because it capture the period when climate change signals were not an issue and when they are stronger .